2020
DOI: 10.48550/arxiv.2012.10106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable Implementation of Probabilistic ODE Solvers

Abstract: Probabilistic solvers for ordinary differential equations (ODEs) provide efficient quantification of numerical uncertainty associated with simulation of dynamical systems. Their convergence rates have been established by a growing body of theoretical analysis. However, these algorithms suffer from numerical instability when run at high order or with small step-sizes-that is, exactly in the regime in which they achieve the highest accuracy. The present work proposes and examines a solution to this problem. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Implementation The implementation follows the practices suggested by Krämer and Hennig (2020) and includes exact initialization, preconditioned state transitions, and a square-root implementation. All experiments are implemented in the Julia programming language (Bezanson et al, 2017).…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation The implementation follows the practices suggested by Krämer and Hennig (2020) and includes exact initialization, preconditioned state transitions, and a square-root implementation. All experiments are implemented in the Julia programming language (Bezanson et al, 2017).…”
Section: Case Studiesmentioning
confidence: 99%
“…This paper builds on probabilistic numerical ODE solvers based on Bayesian filtering and smoothing (Schober et al, 2019;Tronarp et al, 2019). These "ODE filters" have been shown to converge with polynomial rates (Kersting et al, 2020;Tronarp et al, 2021) and their efficiency has been demonstrated on a range of both non-stiff and stiff problems (Krämer and Hennig, 2020;Bosch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Probabilistic numerical algorithms respond to these challenges by solving problems of numerical simulation with probabilistic inference. For initial value problems, probabilistic solvers share lineartime complexity, adaptive step-size selection, and high polynomial convergence rates with their non-probabilistic counterparts [4][5][6][7], and further provide functionality to quantify uncertainty within probabilistic programs [8,9].…”
Section: Boundary Value Problems In Computational Pipelinesmentioning
confidence: 99%
“…If the BVP is non-linear, the EKS introduces a significant linearisation error wherever the predictive distribution deviates strongly from the true posterior. Unfortunately, in its standard implementation, the EKS necessarily starts with incomplete information about the state y(t 0 ) and higher-order derivatives (initialisation of which is crucial to probabilistic initial value problem solvers as well [7]). Ensuring that the prior distribution satisfies the boundary conditions by construction solves this problem because the iteration can never drift too far away from the optimum.…”
Section: Initialisation With An Extended Kalman Smoothermentioning
confidence: 99%
See 1 more Smart Citation